2015
DOI: 10.1080/18146627.2015.1036570
|View full text |Cite
|
Sign up to set email alerts
|

Educational Infrastructure and Resources for Sustainable Access to Schooling and Outcomes: The Case of Early Literacy Development in Southern Tanzania

Abstract: Following on the 1990 and 2000 World Conferences on Education for All, African governments increased their focus on access to schooling (but not necessarily on outcomes) by providing more facilities for increased enrolments. The learning outcomes that had been neglected led to a call to focus on more sustainable access-reexamining the quality of some of those facilities against the anticipated quality of educational outcomes. Studies in Southern and Eastern Africa, including the one under discussion here, indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 3 publications
2
9
0
Order By: Relevance
“…Four classrooms lacked any materials on display, walls were empty and resources were non-existent. Similar portrayal of dark, colourless classrooms is noted in the Ngwaru and Oluga (2015) study in poor schools in Tanzania.…”
Section: Classroom Organisationsupporting
confidence: 78%
See 1 more Smart Citation
“…Four classrooms lacked any materials on display, walls were empty and resources were non-existent. Similar portrayal of dark, colourless classrooms is noted in the Ngwaru and Oluga (2015) study in poor schools in Tanzania.…”
Section: Classroom Organisationsupporting
confidence: 78%
“…Research in Africa reinforces the view that children from low‐income families are at risk of learning outcome difficulties, particularly in literacy. The Ngwaru and Oluga (, p. 88) study in low‐resourced communities in Tanzania noted the extent to which school infrastructure and ecology including buildings, teaching learning materials and teacher characteristics reinforced literacy practices and events at home and school. Similarly, a Kenyan study by Piper et al () found that poverty, literacy skills and weak instructional methods combined to drastically limit the educational opportunities for poor children.…”
Section: Literacy Policy and Practicementioning
confidence: 99%
“…Provision of school facilities is very important and the maintenance of facilities is a condition that is also important for improving the good academic environment. The learning process will be more effective and quality if supported by adequate facilities and infrastructure, one of which is in literacy activities (Ngwaru & Oluga, 2015). The learning process is a series of activities carried out by teachers and students by utilizing the facilities and infrastructure available to obtain optimal learning outcomes (Vivian, Nkong, George, & Mohamadou, 2016 role and is needed for the smooth learning process.…”
Section: Maintenance Of Educational Facilities and Infrastructurementioning
confidence: 99%
“…These facilities will affect the quality of education. Students will be better able to receive learning well if they can use physical facilities directly (Ngwaru & Oluga, 2015). This also has an impact on classroom conditions that are more enjoyable for students.…”
Section: Introductionmentioning
confidence: 99%
“…Most schools are characterized by ramshackle infrastructure. In addition, new programs and expanded intake have been suggested without matching development of the physical infrastructure (Ngwaru and Oluga, 2015). The available inadequate infrastructure, due to poor management, has continued to dilapidate.…”
Section: Introductionmentioning
confidence: 99%